Delusions in Context (Springer International Publishing, 2018)
'This is an excellent and engaging resource on delusions. The idea that delusions should not be seen as radically different from other beliefs... is an important challenge to much contemporary thinking and practice. It should be of interest to anyone studying delusional beliefs, and to all those who aim to help people who are troubled by them.' Philippa A Garety, Professor of Clinical Psychology, King's College London, UK 'This book provides a powerful defence of the continuity between delusional beliefs and non-delusional beliefs. It is a remarkable example of productive interactions between different research areas concerning a topic of common interest.' Kengo Miyazono, Associate Professor, Hiroshima University, Japan This open access book offers an exploration of delusions-unusual beliefs that can significantly disrupt people's lives. Experts from a range of disciplinary backgrounds, including lived experience, clinical psychiatry, philosophy, clinical psychology, and cognitive neuroscience, discuss how delusions emerge, why it is so difficult to give them up, what their effects are, how they are managed, and what we can do to reduce the stigma associated with them. Taken as a whole, the book proposes that there is continuity between delusions and everyday beliefs. It is essential reading for researchers working on delusions and mental health more generally, and will also appeal to anybody who wants to gain a better understanding of what happens when the way we experience and interpret the world is different from that of the people around us. Lisa Bortolotti is Professor of Philosophy at the University of Birmingham, UK. She works in the philosophy of the cognitive sciences and has a special interest in belief, irrationality, and mental health.